2020
DOI: 10.1371/journal.pone.0228984
|View full text |Cite
|
Sign up to set email alerts
|

Severe obesity and the impact of medical weight loss on estimated glomerular filtration rate

Abstract: Objective To assess the impact of obesity, glucose tolerance, and weight loss on renal function, we measured serum creatinine and cystatin C and estimated glomerular filtration rate (GFR) indexed to 1.73m 2 body surface area (BSA) and GFR indexed to actual BSA in subjects with normal and abnormal glucose tolerance before and up to 2 years after medical weight loss. Methods We studied 146 subjects at baseline and 3-to-6 months after 18% reduction in weight; 43 were also studied at 2-years. GFR was estimated usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 18 publications
4
14
0
2
Order By: Relevance
“…Our results show that, despite the absence of type 2 diabetes, using EPI formula with non‐indexed GFR, HF is present in a large percentage of cases (35%). This is in keeping with other studies showing that subjects with severe obesity have higher measured creatinine clearance and eGFR than people of normal weight 24,25 . In fact, in severe obesity, BMI reflects not only a disproportionate amount of fat mass, but also an increase in lean mass, which is known to provide the greatest contribution to the circulating levels of creatinine 22 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results show that, despite the absence of type 2 diabetes, using EPI formula with non‐indexed GFR, HF is present in a large percentage of cases (35%). This is in keeping with other studies showing that subjects with severe obesity have higher measured creatinine clearance and eGFR than people of normal weight 24,25 . In fact, in severe obesity, BMI reflects not only a disproportionate amount of fat mass, but also an increase in lean mass, which is known to provide the greatest contribution to the circulating levels of creatinine 22 .…”
Section: Discussionsupporting
confidence: 91%
“…showing that subjects with severe obesity have higher measured creatinine clearance and eGFR than people of normal weight. 24,25 In fact, in severe obesity, BMI reflects not only a disproportionate amount of fat mass, but also an increase in lean mass, which is known to provide the greatest contribution to the circulating levels of creatinine. 22 Our study shows a strong association between lean mass and risk of HF, similarly to previous reports in morbidly obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, cystatin C synthesis has been shown to be upregulated in adipose tissue in obese individuals and to counteract inflammation of peripheral insulin-sensitive tissues [ 41 ]. Recently it has been shown that in severely obese subjects enrolled in medical weight loss programmes, cystatin C–based eGFR and indexation to actual body surface area (BSA) instead of 1.73 m 2 may provide the most accurate estimate of kidney function [ 42 ]. Also, Chang et al [ 43 ] assessed kidney function before and after bariatric surgery and observed a decrease in absolute iohexol clearance, while the creatinine-based eGFR overestimated and the cystatin C-based eGFR underestimated mGFR.…”
Section: Effect Of Body Compositionmentioning
confidence: 99%
“…В нашем исследовании было подтверждено, что у больных неосложненной ГБ без ХБП при увеличении цистатина С до 1016 нг/мл и выше и снижении СКФ (CKD-EPIcys) до 74 мл/мин/1,73 м 2 и ниже наличие НТГ, ДД ЛЖ, ГЛЖ и увеличения ИОЛП не только дополнительно увеличивают риск развития ХСН, но могут быть самостоятельными маркерами увеличения цистатина С и снижения СКФ. Так, в исследовании Rothberg AE, et al (2020) у больных с тяжелым ожирением, которые снижали массу тела на величину до 18% от исходной, было найдено, что по мере уменьшения гиперинсулинемии с высокой частотой регистрировалась гиперфильтрация (рСКФ ≥135 мл/мин), оцененная по СКФ, основанной в большей степени на определении цистатина С [19]. В одном из экспериментальных исследований было найдено, что НТГ также связано и с канальцевой дисфункцией [20].…”
Section: Discussionunclassified